Crush - Chmakova, Svetlana, 1979- (New York, NY : JY, 2018)
"When the group dynamic among Jorge's friends starts to shift, he must learn to balance what his friends expect of him and what he really wants.".
5-8.
Keywords: Clubs -- Comic books, strips, etc -- Juvenile fiction; Middle schools -- Comic books, strips, etc -- Juvenile fiction; Popularity -- Comic books, strips, etc -- Juvenile fiction; Schools -- Comic books, strips, etc -- Juvenile fiction; Clubs -- Fiction; Middle schools -- Fiction; Popularity -- Fiction; Schools -- Fiction; Clubs -- Comic books, strips, etc -- Fiction; Middle schools -- Comic books, strips, etc -- Fiction; Popularity -- Comic books, strips, etc -- Fiction; School stories; Graphic novels